Two Binding Sites for [3H]PBR28 in Human Brain: Implications for TSPO PET Imaging of Neuroinflammation - Owen, David R; Howell, Owain W; Tang, Sac-Pham; Wells, Lisa A; Bennacef, Idriss; Bergstrom, Mats; Gunn, Roger N; Rabiner, Eugenii A; Wilkins, Martin R; Reynolds, Richard; Matthews, Paul M; Parker, Christine A (Journal of cerebral blood flow and metabolism, 2010)
[11C]PBR28, a radioligand targeting the translocator protein (TSPO), does not produce a specific binding signal in approximately 14% of healthy volunteers. This phenomenon has not been reported for [11C]PK11195, another TSPO radioligand. We measured the specific binding signals with [3H]PK11195 and [3H]PBR28 in brain tissue from 22 donors. Overall, 23% of the samples did not generate a visually detectable specific autoradiographic signal with [3H]PBR28, although all samples showed [3H]PK11195 binding. There was a marked reduction in the affinity of [3H]PBR28 for TSPO in samples with no visible [3H]PBR28 autoradiographic signal (Ki=188±15.6 nmol/L), relative to those showing normal signal (Ki=3.4±0.5 nmol/L, P<0.001). Of this latter group, [3H]PBR28 bound with a two-site fit in 40% of cases, with affinities (Ki) of 4.0±2.4 nmol/L (high-affinity site) and 313±77 nmol/L (low-affinity site). There was no difference in Kd or Bmax for [3H]PK11195 in samples showing no [3H]PBR28 autoradiographic signal relative to those showing normal [3H]PBR28 autoradiographic signal. [3H]PK11195 bound with a single site for all samples. The existence of three different binding patterns with PBR28 (high-affinity binding (46%), low-affinity binding (23%), and two-site binding (31%)) suggests that a reduction in [11C]PBR28 binding may not be interpreted simply as a reduction in TSPO density. The functional significance of differences in binding characteristics warrants further investigation.